MONOCULTURE OF SILVER BARB (BARBODES GONIONOTUS) VS. MIXED CULTURE WITH GIFT (OREOCHROMIS NILOTICUS) IN SEASONAL MINI PONDS UNDER FARMING SYSTEM IN BANGLADESH (Biological Sciences - PJSIR, 2004)
The comparative production performance and the feasibility of production of fish in unutilized seasonal mini ponds under farmer’s condition through culturing silver barb (Barbodes gonionotus Bleeker) in mono and mixed culture with Geneti- cally Improved Farmed Tilapia (GIFT) (Oreochromis niloticus.L) was investigated in six seasonal mini ponds of 0.02 ha each for five months. Silver barb mono culture (Treatment-1) and mixed culture (Treatment-2) with GIFT were tested with stocking density of 16,000/ha of fish for both treatments. There was no significant variation on either water quality parameters or abundance of planktonic organisms due to different culture systems of silver barb. In mixed culture (T2) system, GIFT ranked 1st  position in the production (1442.90 kg/ha) and the individual production of silver barb was856.36 kg/ha. A significantly (P < 0.05) higher total production (2299.26 kg/ha) of fish and net benefit (58, 383.12 TK/ha or US$ 1004/ha) was recorded in the mixed culture (T2) than that of the total production (1606.53 kg/ha) and net benefit (31, 774.26 TK/ha or US$ 546.42/ha) of monoculture system  (T1).